Constructing teacher identity in a Chemistry and Biology teaching degree course: curricular contributions (Olhar de Professor, 2021)
The objective of this work was to investigate the contribution of the curricular configuration of a Dual Degree Course in Biology and Chemistry (LDBQ), of a Higher Education Institution in the North of the country, in the construction of the teaching identity. Data collection was based on the documentary analysis of the Pedagogical Project of the Course, using Textual Discursive Analysis. The results show that the LDBQ was created to meet the needs of the local context, for teachers with training in Biology and Chemistry. The professional profile and identity of the course point to a professional who will work in Basic Education and in other segments, as a technical performance at a higher level. And yet, training principles were observed, such as contextualization, interdisciplinarity, articulation between theory and practice, didactic transposition and research in teaching. However, there is a need to integrate specific knowledge in the areas of Biology and Chemistry with pedagogical ones.
Keywords: Teacher Education. Curriculum. Teacher Identity.